The molecular mechanisms of Monascus purpureus M9 responses to blue light based on the transcriptome analysis - Di Chen (Nature Portfolio, 2017)
Abstract Light is an important environmental factor that regulates various physiological processes of fungi. To thoroughly study the responses of Monascus to blue light, transcriptome sequencing was performed on mRNAs isolated from samples of Monascus purpureus M9 cultured under three conditions: darkness (D); exposure to blue light for 15 min/d (B15); and exposure to blue light for 60 min/d over 8 days (B60). The number of differentially expressed genes between the three pairs of samples—B15 vs D, B60 vs B15, and B60 vs D—was 1167, 1172, and 220, respectively. KEGG analysis showed the genes involved in primary metabolism including carbon and nitrogen metabolism were downregulated by B15 light treatment, whereas B15 upregulated expression of genes involved with aromatic amino acid metabolism, which associated with development, and branched chain amino acid metabolism, and fatty acid degradation, which can produce the biosynthetic precursors of pigments. When exposed to B60 conditions, genes with roles in carbohydrate metabolism and protein synthesis were upregulated as part of a stress response to blue light. Based on this study, we propose a predicted light-stimulated signal transduction pathway in Monascus. Our work is the first comprehensive investigation concerning the mechanism of Monascus responses to blue light.